The Role of Islam in Building Interfaith Tolerance in Indonesia - Susi Apriudianisti (Formad English Foundation NTB Jakarta, 2025)
Indonesia, as a country with diverse religions, cultures, and ethnicities, faces challenges in maintaining social harmony. Interfaith tolerance is a key factor in creating a peaceful and prosperous life. Islam, as the majority religion in Indonesia, plays a significant role in fostering tolerance through its teachings that emphasize compassion (rahmah), wisdom (hikmah), and justice. This study aims to analyze the role of Islam in building interfaith tolerance in Indonesia through a literature review. The method used is a qualitative literature study, examining various primary and secondary sources, including the Qur'an, Hadith, and previous research. The findings show that Islam contributes to building tolerance through education, preaching, and religious institutional policies. The role of religious counselors, Islamic Religious Education (PAI) teachers, and preachers (da'i) is crucial in instilling tolerance within society. Additionally, cooperation between Islamic organizations and the government in formulating policies on religious moderation strengthens social harmony. However, challenges such as radicalism and the spread of hoaxes still hinder the realization of ideal tolerance. Therefore, a more comprehensive strategy is needed to strengthen Islam's role as an agent of tolerance in Indonesia.